A Conservative Management Approach for Unusual Presentation of Oral Actinomycosis - Qamar Hashem (Hindawi Limited, 2021)
Actinomycosis is gram-positive saprophytic infection that is characterized by chronic suppurative and granulomatous lesion. It could be found in the oral cavity, lungs, colon, and genital area. In the oral cavity, it is commonly associated with infected root canals presented as persistent infections. This case reports demonstrate an atypical presentation of actinomycosis in the lower left mandibular canine/premolar area showing painless soft tissue lesion associated with bone sequestration. Nonsurgical curettage of the lesion followed by nonsurgical root canal treatment and retreatment to the offended teeth was determined as the treatment modality for this case.